Diastolic pressure indices offer a novel approach to predicting risk of graft loss after pediatric heart transplant. (3rd February 2018) - Albers, Erin L.; Bradford, Miranda C.; Friedland‐Little, Joshua M.; Hong, Borah J.; Kemna, Mariska S.; Chen, Jonathan M.; Law, Yuk M.
Abstract: PH is a risk factor for GL after HTx. However, traditional parameters are not reliable predictors of risk in children. We hypothesized that DPI (dPAP and DPG) are predictive of GL in pediatric HTx recipients. The UNOS/SRTR database was reviewed to identify pediatric HTx recipients (age <18 years) between 1994 and 2013. Recipients with pretransplant hemodynamic data were grouped by diagnosis (CMP or CHD), and the groups were analyzed separately. Bivariate Cox regression analysis examined the association between hemodynamic variables and GL. DPI showed the strongest association with early GL in recipients with CMP (dPAP: HR = 1.25 [1.09‐1.42]; DPG: 1.24 [1.11‐1.38]). Among CHD recipients, DPI were associated with early GL in those with preexisting PH (dPAP: HR = 1.16 [1.01‐1.33]; DPG: HR = 1.10 [1.00‐1.21]). No cutoff values for "high‐risk" DPI were identified, but a continuous relationship between higher DPI and risk of early GL was observed. DPI are associated with early GL in select pediatric HTx recipients. Our findings suggest that DPI should be considered as part of routine hemodynamic assessment for pediatric HTx candidates.